The Moderating Influences of Emotional Pretensions and Dogmatic Behaviors on the Relationship between Leadership-Induced Stress and Mental Well-Being - Ayodeji, Folusho; Lawal, Olufemi A. (Advances in Social Sciences Research Journal, 2021)
This study examines the moderating influences of emotional pretensions and dogmatic behaviours on the relationship between leadership-induced stress and mental well-being. 253 employees across several branches of four major banks in Nigeria, all of which were at the final stages of their merger to or acquisition by another bank at that time, participated in the study. A moderated regression analysis confirmed the main propositions of the study that leadership-induced stress will jeopardize mental health. Analysis showed that leadership-induced stress negatively predicted mental health. Emotions Hiding and Dogmatic Behavior also predicted mental health. While emotions hiding negatively predicted mental health, dogmatic behaviour predicted it positively. As expected, leadership-induced stress*dogmatic behaviour interaction significantly predicted mental health. But contrary to expectation, leadership-induced stress*Emotions Hiding interaction did not predict mental health. This suggests that the adverse influence of employees’ high emotions hiding on their mental health (found in this study) did not depend on their experience of leadership-induced stress. These results were discussed in the light of reviewed literature. KEYWORDS: Leadership-Induced Stress, Mental Wellbeing, Emotional Pretensions, Dogmatic Behaviours, Emotions Hiding